Prognostic biomarker and clinical significance of PLOD gene family in clear cell renal cell carcinoma - Shang, Xuan; Liu, Liu; Yang, Zhenwei; Yan, Min; Ren, Ruimin; Guo, Kexin; Wang, Jie; Zhang, Wei; Chang, Jiasong; Li, Jialei; Cao, Jimin; Li, Guang; et al. (Frontiers in Oncology, 2025)
BackgroundThe PLOD gene family, involved in extracellular matrix (ECM) remodeling, plays a role in tumor progression, but its comprehensive role and clinical significance in clear cell renal cell carcinoma (ccRCC) remains unclear.MethodsWe integrated multi-omics bioinformatics analyses from public databases (TCGA, GEO) with experimental validation using RT-qPCR, western blotting, and functional assays to systematically evaluate the expression patterns, prognostic value, immune microenvironment associations and drug resistance of PLOD genes in ccRCC. Computational approaches, including the comparative toxicogenomics database and molecular docking, were further employed to identify potential chemical modulators.ResultsPLOD1, PLOD2, and PLOD3 were consistently overexpressed at both mRNA and protein levels in ccRCC tissues and cell lines. High PLOD expression was significantly correlated with reduced overall survival, and poor disease-free survival. Functional enrichment analysis revealed the involvement of PLOD gene family in collagen biosynthesis, ECM-receptor interaction, and lysine degradation pathways. PLOD expression was also linked to an immunosuppressive microenvironment and resistance to conventional therapeutics. Through toxicogenomics screening and molecular docking, acetaminophen was identified as a potential regulator of all three PLOD proteins.ConclusionsThis study underscores the pivotal role of the PLOD family in ccRCC pathogenesis through ECM remodeling, immune modulation, and therapy resistance. Our results support their utility as diagnostic and prognostic biomarkers, and acetaminophen may serve as a candidate for targeting PLOD-mediated pathways, providing a foundation for future preclinical and therapeutic investigations.